AB1281 Making a diagnosis and predicting prognosis of bone structure by low field compact magnetic resonance imaging machine in patients with rheumatoid arthritis. (23rd January 2014) - Sugihara, M.; Okamoto, Y.; Hirota, T.; Suzuki, T.; Horikoshi, M.; Hagiya, C.; Miki, H.; Yokosawa, M.; Hagiwara, S.; Takano, Y.; Umeda, N.; Kondo, Y.; et al.
Abstract : Background: Magnetic resonance imaging (MRI) is able to detect synovitis, bone marrow edema and bone erosion, which X-ray radiograph is not. This modality of imaging would be helpful in clinical practice in rheumatic diseases. Objectives: To assess the usefulness of low field MRI to make a diagnosis of rheumatoid arthritis (RA), and to predict future bone destruction. Methods: We developed 0.3 tesla low field compact MRI (cMRI). All the patients who underwent examination by cMRI were included. T1 weighted image and short tau inversion recovery image of both hands were taken. We scored every site for 0-3 points by compact MRI score [1] as degree of affection; 23 sites for bone erosion, 23 sites for bone marrow edema and 11 sites for synovitis. Of all RA patients, those who had 2 sequential examinations with 6 to 12 months interval were analyzed to find the poor prognosis factor of bone destruction. Results: Five hundreds and sixty four hands of 283 patients were included and divided into 4 groups; 168 hands of 84 patients were RA treated with biologic agents (infliximab 37 patients, etenercept 23, tocilizumab 13, adalimumab 6 and abatacept 5) (Group 1), 209 hands of 105 patients were RA treated without biologic agent (Group 2), 54 hands of 27 patients had arthralgia or synovitis caused by other connective tissue diseases (Group 3) and 133 hands of 67 patients were undifferentiated arthritis (Group 4). Erosion score, bone marrow edema score and synovitis score in group 1, 2 and 3 were significantly higher than that of Group 4 (erosion score; 19.13±14.37, 11.40±11.32, 6.98±11.67 and 1.94±2.42 for group 1 to 4 respectively, bone marrow edema score; 2.55±6.62, 1.18±4.47, 0.66±6.00 and 0.25±1.92, synovitis score; 5.16±6.43, 3.57±3.89, 1.91±3.04 and 0.64±1.35, p<0.05 for each pair with group 4). One hundred and three hands of 53 RA patients had two sequential examinations. In those patients, synovitis score at the first evaluation was significantly correlated with progression of erosion score 6 to 12 months later (r 2 =0.29, p=0.0031). One synovitis score at the first examination would predict 0.33 point progression in erosion score at the second examination. Conclusions: cMRI examination would be of use to make diagnosis of RA from undifferentiated arthritis. Synovitis observed by cMRI would be a poor prognosis factor of bone destruction. References: Suzuki, et al. Mod Rheumatol 2009, 19, 358 Disclosure of Interest: None Declared